Pengembangan Manajemen Sistem Digital dalam Departemen Warehouse Menggunakan Metode SOAR pada PT. XYZ - Firmansyah, Ryan; Suseno, Agustian; Nugraha, Billy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT. XYZ is a company that operates in the field of gravure printing and flexible packaging. The development of digital-based warehouse management is based on the SOAR (Strengths, Opportunities, Aspirations, and Results) methodology, which in the long term can be used in the field of inventory and also as a strategic planning tool used by organizations to analyze strengths and opportunities and formulate strategic goals with focus. on future goals for appropriate outcomes. The method used is qualitative research observation by analyzing the development of digital system management in the warehouse sector using the SOAR diagram, showing that maximum results can be achieved by analyzing the warehouse management system by considering the SOAR method. The results of the analysis of the development of digital system management in the warehouse department using the SOAR matrix, it can be seen that this was realized because the system has many positive things which are strengths and various opportunities both from an internal and external perspective. One of the strengths of this system is a good system facility with structured goals, both short and long term and based on several strategies that can be taken.